YLE – општи филозофски контексти - Поповска, Јасмина (Филозофско друштво на Македонија, 2017)
Faced with the task to articulate an abstract concept that had no terminological equivalent in the Ancient Greek language before, Aristotle chose one already existent concrete word – ὕλη, and gave it a new abstract meaning. This novelty brought various theoretical confusions and interpretations, which entailed serious issues in its proper translation. This article will make brief overview of the most characteristic meanings of the concept ὕλη in the works of Aristotle in order to establish philosophical background for a proper philological analysis. The article will highlight several main points of the content of this concept: the nature of its existence, the possibility of its knowledge, the nature of πρώτη ὕλη, ὕλη as a cause, ὕλη as potentiality, the nature of hylomorphism, ὕλη as a hypothetical necessity, and ὕλη as a principle of individuation.